Second Language Acquisition Theories as a Framework for Creating Distance Learning Courses - Ariza, Eileen N.; Hancock, Sandra (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2003)
Moore and Kearsley (1996) maintain distance educators should provide for three types of interaction: a) learner-content; b) learner-instructor; and c) learner-learner. According to interactionist second language acquisition (SLA) theories that reflect Krashen’s theory (1994) that comprehensible input is critical for second language acquisition, interaction can enhance second language acquisition and fluency. Effective output is necessary as well. We reviewed the research on distance learning for second language learners and concluded that SLA theories can, and should, be the framework that drives the development of courses for students seeking to learn languages by distance technology. This article delineates issues to consider in support of combining SLA theories and research literature as a guide in creating distance language learning courses.